Doctor-patient communication in the opinion of medical students - Plutecki, Dawid (Logopedia Silesiana, 2021)
Interpersonal communication in medicine is a very important topic that requires constant development and training of health care physicians. The article is a report from a study the aim of which was to find out the opinions of medical students from Polish universities on this subject. The study involved 56 female students and 38 students who answered questions about: communication techniques in the doctor-patient relationship, protocols for passing on unsuccessful information, concerns related to contact with a given patient, communication barriers, the impact of the COVID-19 pandemic on interpersonal communication, departments with which the greatest communication problems are associated, the usefulness of optional classes during the education of students in the field of medicine. The conclusions were presented in the discussion, along with the possibilities of solving potential communication problems in the patient-doctor relationship.